Implementasi Strategi Pemasaran Digital untuk Meningkatkan Daya Saing Bisnis pada Kafe Esteko - Rahman, Abdullah Reza Fatur; Taufik, Muhammad; Aris, Valentino (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
Digital marketing in this study refers to the utilization of internet-based technology as the primary medium for promoting products and building effective relationships with customers. Marketing strategy includes the planning, implementation, and evaluation of promotional activities to achieve Esteko Café’s business objectives. Social media, particularly Instagram, is used as the main platform to deliver attractive, informative, and interactive promotional content aimed at increasing audience engagement. Business competitiveness is defined as Esteko Café’s ability to maintain its advantages amid the increasingly competitive café industry. Customer engagement serves as an indicator of digital marketing success through interactions such as likes, comments, shares, and follower growth. The AIDA model is used to analyze the effectiveness of marketing communication in attracting attention, generating interest, creating desire, and encouraging purchasing actions. In addition, content marketing through relevant and consistent content strengthens customer loyalty and brand image, while supporting the sustainable improvement of business competitiveness in the digital era.